Magnetic compass orientation in two strictly subterranean rodents: learned or species-specific innate directional preference? - Oliveriusová, Ludmila; Nĕmec, Pavel; Králová, Zuzana; Sedláček, František (The Journal of experimental biology, 2012)
Evidence for magnetoreception in mammals remains limited. Magnetic compass orientation or magnetic alignment has been conclusively demonstrated in only a handful of mammalian species. The functional properties and underlying mechanisms have been most thoroughly characterized in Ansell's mole-rat, Fukomys anselli, which is the species of choice due to its spontaneous drive to construct nests in the southeastern sector of a circular arena using the magnetic field azimuth as the primary orientation cue. Because of the remarkable consistency between experiments, it is generally believed that this directional preference is innate. To test the hypothesis that spontaneous southeastern directional preference is a shared, ancestral feature of all African mole-rats (Bathyergidae, Rodentia), we employed the same arena assay to study magnetic orientation in two other mole-rat species, the social giant mole-rat, Fukomys mechowii, and the solitary silvery mole-rat, Heliophobius argenteocinereus. Both species exhibited spontaneous western directional preference and deflected their directional preference according to shifts in the direction of magnetic north, clearly indicating that they were deriving directional information from the magnetic field. Because all of the experiments were performed in total darkness, our results strongly suggest that all African mole-rats use a light-independent magnetic compass for near-space orientation. However, the spontaneous directional preference is not common and may be either innate (but species-specific) or learned. We propose an experiment that should be performed to distinguish between these two alternatives.
Keywords: chování zvířat; druhová specificita; Female; Orientation; krysa rodu Rattus; magnetické pole; zvířata; Darkness; ženské pohlaví; Male; orientace; mikroftalmičtí podzemní hlodavci; Species Specificity; Mole Rats; Rats; Animals; Magnetic Fields; mužské pohlaví; tma; Behavior, Animal